The Legal Framework of the National Independent Regulatory Authority for Audiovisual in Algeria: Between Digital Challenges and International Comparison - Bedrine, Amel (Journal of Ecohumanism, 2026)
With the acceleration of digital transformations, social media platforms have emerged as a key actor in Algeria’s communication landscape, imposing new patterns of content production and circulation that go beyond the boundaries of traditional media regulation. Despite the existence of the Independent National Authority for Audiovisual Regulation as an independent national body, its ability to keep pace with this reality remains questionable, particularly in light of the cross-border nature of digital platforms and the weakness of the legal frameworks governing them.Accordingly, this article seeks to answer the following main question:Is the Independent National Authority for Audiovisual Regulation able to exercise its supervisory functions over content published on digital platforms within the dominance of an open digital space, in accordance with the relevant national legislation?